Incidence and risk factors for chronic kidney disease after hematopoietic stem cell transplantation - Alina Tanase; Andreea Andronesi; Bogdan Sorohan; Andreea Vasile; Lavinia Lipan; Zsofia Varady; Laura Stefan; Oana Craciun; Adela Ranete; Bogdan Obrisca; Rebeca Cioata; Gener Ismail (Renal Failure, 2025)
Background Chronic kidney disease (CKD) in hematopoietic stem cell transplantation (HSCT) is becoming more common. Only few studies were published during the past 10 years. Identification of risk factors is of outmost importance.Objectives We assessed prospectively a cohort of 197 patients who underwent allogeneic HSCT, aiming to evaluate the incidence and risk factors associated with CKD. We registered the persistence of the low GFR. Cox proportional hazard analysis has been used to identify the risk factors.Main results The mean age was 38.7 years (52.8% female). Acute kidney injury was present in 80% patients within 3 months and CKD incidence was 11.7% with a median onset of 6 months. By univariate Cox regression analysis, age (per 1 year) was the only variable associated with CKD (HR= 1.06, 95%, CI= 1.02–1.10, p = 0.001) and baseline creatinine (per 1 mg/dl) presented a trend of association (HR= 4.62, 95%, CI= 0.75–28.42, p = 0.09). Multivariate Cox regression analysis showed that age (per 1 year; HR= 1.08, 95%, CI = 1.02–1.14, p = 0.003) and hematologic disease length (per 1 month; HR = 1.01, 95%, CI= 1.001–1.02, p = 0.02) were positive predictors for CKD, whereas acute lymphoblastic leukemia (HR= 0.37, 95%, CI= 0.20–0.61, p = 0.02) was a negative predictor factor, being associated with a 63% reduction risk for developing CKD.Conclusions As the prognostic of hematopoietic stem cell transplantation survivors is improving, CKD emerges as an important comorbidity, with hematologic disease length and baseline eGFR being independent risk factors for renal dysfunction.